PROSES COLLABORATIVE GOVERNANCE DALAM PENCEGAHAN PERKAWINAN ANAK DI KABUPATEN JEPARA - Uswatun Khasanah Billillah; Augustin Rina Herawati (Journal of Management and Public Policy, 2026)
Child marriage remains a serious social problem in Indonesia due to its impact on education, reproductive health, and children’s welfare. Although the minimum age for marriage has been raised to 19 years through Law Number 16 of 2019, the practice of child marriage still occurs through marriage dispensation mechanisms in the courts. In Jepara Regency itself, the number of marriage dispensation recommendations fluctuates, necessitating more systematic prevention efforts. This study aims to analyze the collaborative governance process in preventing child marriage in Jepara Regency and identify factors influencing this collaborative process. This study uses a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. Data analysis was conducted using an interactive analysis model that includes data reduction, data presentation, and drawing conclusions. The research analytical framework uses the collaborative governance theory of Ansell and Gash, which emphasizes face-to-face dialogue, trust-building, commitment to the process, shared understanding, and interim results. The results show that the collaborative process has been carried out through socialization activities, marriage dispensation counseling, and coordination between the Religious Court and the DP3AP2KB. However, this collaboration has not been optimal due to the lack of specific regulations, incidental coordination, and the dominance of curative rather than preventive approaches. Therefore, strengthening institutional design, clear regional regulations, and increasing the participation of various actors are needed to strengthen the collaborative governance process in preventing child marriage in Jepara Regency.